ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR BPKP (Studi Pada Auditor Perwakilan Badan Pengawasan Keuangan dan Pembangunan Provinsi Riau) - Rosliana Rosliana (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The study aimed to understand influence of independency, comprehension of good governance and audit structure on BPKP auditors’ performance. Data was obtained by spreading questionnaires to the auditors who work at BPKP of Riau Representation Office. The selection of sample using incidental sampling method. The number of questionnaires distributed was 60 copies, but only 36 questionnaires returned, 31 questionnaires which the data could be analyzed to be used as the sample as the sample for this study. Analysis of data in this study using multiple regression analysis whith SPSS Windows Program version 20. The dependent variable is BPKP auditor’s performance, and the independent variable are independency, comprehension of good governance and audit structure. The result shows that independency has significant influence on BPKP auditors’ performance, but comprehension of good governance and audit structure do not have a significant effect on BPKP auditors’ performance.